Malaysian users’ perception towards facebook as a social networking site - Haque, A. K. M. Ahasanul; Sarwar, Abdullah Al-Mamun; Yasmin, Farzana (Human Resource Management Academic Research Society, 2013)
Social network sites constitute a rapidly growing phenomenon. Thus, understanding users perception toward social network sites become essential. Realizing this present needs, this study strives to determine the user’s perception towards Facebook in Malaysia. This paper commences by examining the relevance of the privacy, features, sharing social information, and accessibility provided by the social network sites. A self-administered questionnaire survey was conducted. A convenience sampling method was employed to collect data. A total of 206 questionnaires were found valid out of total 250 distributed questionnaires. Results indicate that there is a positive perception of Facebook in Malaysia exists because of easy accessibility and variety of features. However, Facebook still needs to improve the privacy system to protect the sharing social information by the users to make the Facebook more acceptable for the users in Malaysia.